Effects of calcium chelation on the neutralization of milk protein isolate and casein micelle reassembling. (1st December 2020) - Wu, Shaozong; Fitzpatrick, John; Cronin, Kevin; Miao, Song
Highlights: Using citric acid for neutralization produced chelating agent citrate. Calcium was mostly chelated during neutralization. Neutralized milk protein solutions suggested a casein equilibration at around pH 8. Neutralized MPI obtained slight increase particle size compared with alkalized MPI. Abstract: Rehydration in an alkaline solution has been shown to improve the rehydration behaviour of milk protein isolate (MPI). In this study, the focus is on citric acid neutralization of MPI powder dissolved in alkaline solution. The results showed that alkalization induced more negative zeta-potential compared to MPI control, reducing it from –22.4 mV to –32.6 mV. Neutralization had a relatively similar zeta-potential value as alkalized sample. Sodium carbonate addition increased pH and caused a consequential reduction of ionic calcium in aqueous phase and, neutralization caused a small increase in ionic calcium. Soluble aggregate of κ-casein protein and whey protein was suggested in alkalization and neutralization process by non-reducing SDS-PAGE. In addition, neutralization kept a stable colloidal particle size for pHs decreased to pH 9, 8 and 7; however, alkalization and neutralization created casein aggregates of larger colloidal particle size than primary casein micelle in control MPI.